The city park space as sphere of walking practice - Петренко-Лисак, А. О. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2016)
The article is described the space of city park. City park is a specific environment to objectification everyday and leisure people practices. By the data analyze, we identified the main impressions of the park areas as pleasant/unpleasant, dangerous/safe, and determined eligibility kinds of activities in the park space for urban dwellers. Particular attention is paid to this kind of practice as a walk, because respondents identified it as the most acceptable form of practice in the park. The article is analyzed cultural, sociological and anthropological aspects of the walk, its value and role in the life of a city dweller. We described park space as a part of life practices of urban dwellers, as well as space projects of urban activists.